The Effectiveness of Congklak Traditional Games on Students with Emotional and Behavioral Disorder - Mely Widyaningsih; Sugini Sugini; Mohammad Anwar (Department of Special Education, 2020)
The purpose of this study was to determine the effect of traditional Congklak games on students with emotional and behavioral disorder social interactions in SLB E Bhina Putera. The study used a Single Subject Research (SSR) design. The person as a research subject is AS class III students. Based on the observation, AS shows some examples of its communication with the classmates that is sunken, rarely talk with friends, ignore the teacher's orders, always seen alone on rest hour. The results shows an increase in social interaction through the traditional game of Congklak. With all that set, it can be concluded that the use of Congklak traditional games can have a positive effect on the social interaction of students with emotional and behavioral disorder in SLB E Bhina Putera Surakarta.